2019
DOI: 10.1101/835082
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

C9orf72-derived arginine-containing dipeptide repeats associate with axonal transport machinery and impede microtubule-based motility

Abstract: Hexanucleotide repeat expansions in the C9orf72 gene are the most common genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). How this mutation leads to these neurodegenerative diseases remains unclear. Here, we use human induced pluripotent stem cell-derived motor neurons to show that C9orf72 repeat expansions impair microtubule-based transport of mitochondria, a process critical for maintenance of neuronal function. Cargo transport defects are recapitulated by treating heal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 115 publications
3
40
1
Order By: Relevance
“…Consistently, treatment of iPSC-derived control MNs with recombinant DPRs of only 20 repeats were shown (currently under revision at Science translational medicine) to be sufficient to inhibit the microtubule-based motor proteins kinesin-1 and dynein in axons (48).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Consistently, treatment of iPSC-derived control MNs with recombinant DPRs of only 20 repeats were shown (currently under revision at Science translational medicine) to be sufficient to inhibit the microtubule-based motor proteins kinesin-1 and dynein in axons (48).…”
Section: Discussionmentioning
confidence: 85%
“…We DPRs provides already itself a sufficient explanation of the underlying mechanism as a pending report (under review at Science translational medicine) shows that DPRs can directly inhibit microtubule-based axonal transport of mitochondria and RNA granules by interfering with kinesin-1 and dynein in vivo as well as in vitro-recapitulated (i.e. cell-free) motility assays using recombinant DPRs (48). Moreover, we found augmented DSBs at D80 concurring with DPR foci within same MNs in C9 and C9-KO ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…supra), most C9 patient iPSC-derived neurons exhibit an overall reduction (50%) in C9orf72 transcripts (Table 2) [3,29,78,104,117]. On the contrary, a recent study did not observe these changes in individual and total transcript levels [40]. Also, fibroblasts and iPSCs do not show these consistent transcript alterations (Table 2) [3,29,40,98].…”
Section: C9 Patient-derived Modelsmentioning
confidence: 91%
“…While another study has shown that age-dependent organelle transport defects in iPSC-derived motor neurons from ALS patients carrying TARDBP mutations is independent from TDP-43 aggregation [31], thus, a clear interplay between TDP-43 aggregation and axonal transport still needs to be clarified. Recently, we found that arginine-rich dipeptide repeat proteins (DPRs), which are the pathological translational products from C9orf72 repeat expansion, can cause axonal transport defects in human stem cell-derived motor neurons [32]. We found that several components of the axonal transport machinery interact with arginine-rich DPRs both in vitro and in vivo.…”
Section: Interplay Between Axonal Transport Defects With Other Als Pamentioning
confidence: 99%
“…We found that several components of the axonal transport machinery interact with arginine-rich DPRs both in vitro and in vivo. It has been proposed that argininerich DPRs might directly affect axonal transport through an inhibitory interaction with the microtubule-based transport machinery [32].…”
Section: Interplay Between Axonal Transport Defects With Other Als Pamentioning
confidence: 99%